A systematic review on the use of the breast lesion excision system in breast disease - Wendelien B. G. Sanderink; Babette I. Laarhuis; Luc J. A. Strobbe; Ioannis Sechopoulos; Peter Bult; Nico Karssemeijer; Ritse M. Mann (Insights into Imaging, 2019)
Abstract Purpose To outline the current status of and provide insight into possible future research on the breast lesion excision system (BLES) as a diagnostic and therapeutic device. Methods A systematic search of the literature was performed using PubMed, Embase, and the Cochrane databases to identify relevant studies published between January 2002 and April 2018. Studies were considered eligible for inclusion if they evaluated the diagnostic or therapeutic accuracy or safety of BLES. Results Ultimately, 17 articles were included. The reported underestimation rates of atypical ductal hyperplasia and ductal carcinoma in situ (DCIS) ranged from 0 to 14.3% and from 0 to 22.2%, respectively. Complete excision rates for invasive ductal carcinoma and DCIS ranged from 5.3 to 76.3%. Bleeding was the most frequently reported complication (0–11.8%). Device-related complications may arise, with an empty basket being the most common (0.6–3.6%). Thermal damage of the specimen, caused by the use of a radiofrequency cutting wire, was reported in eight of the included studies. Most thermal artifacts were reported as superficial and small (0.1–1.9 mm). Conclusions The BLES, an automated, image-guided, single-pass biopsy system for breast lesions using radiofrequency is designed to excise and retrieve an intact tissue specimen. It is an efficient and safe breast biopsy method with acceptable complication rates, which may be used as an alternative to vacuum-assisted biopsies. The variable rate of complete excision raises questions about the possibility to use BLES as a therapeutic device for the excision of small lesions. Further research should focus on this aspect of BLES.